(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cross-Cutting Concerns are the part of design pattern and application architecture in software development process where several system and allied concerns are handles in an independent manner saving time of application development. Programming languages tend to focus more on Business Logic implementation and no other aspects like input validation, access control, transaction management, inputoutput validation, error handling, and in some cases session management. Here in this paper we consider how cross-cutting concerns is implemented in different from object oriented programming languages and platforms.